Proteins in Complementary Food: What Is the Healthiest Level? - О. K. Netrebenko; М. I. Dubrovskaya ("Paediatrician" Publishers LLC, 2015)
Adequate protein consumption in infants is a heavily debated issue. First, it is related to the formation of a new scientific field - "Infant prerequisites of man's wellness and illness," which directly indicates that excessive intake of proteins during infancy has long-term consequences and greatly contributes to obesity and chronic infectious diseases in adults; second, it is related to new technologies, which improve the protein component of infant formulas and bring them at par with breast milk in terms of quality and quantity. High protein consumption is related to bottle feeding, because starter and further infant formulas are richer in protein than breast milk. Protein-rich menus trigger production of insulinogenic amino acids, insulin and the insulin-like growth factor (IGF-1). High IFTcombined with branched-chain amino acids (leucine, valine, isoleucine, threonine) activates a set of signalling molecules (mTOR), which are responsible for integrating metabolic and immune response. Repeated activation of mTOR coupled with regular intake of high-protein infant formulas causes health issues in adulthood. Diseases like diabetes type 2, obesity, arterial hypertension, cancer (particularly prostatic cancer), are related to overactivation of the mTOR signalling molecule complex. Intensive consumption of milk in today's world is the key mTOR activator contributing to an increased risk of lifestyle diseases and triggering the mechanism of their development. The progressing infant formula industry allows to cut protein levels in starter and further infant formulas down to 12 g/l and, respectively, lower the risk of non-infectious diseases in adulthood.